Evaluation of Selected Essential Elements in Khalas Dates from Date Palm Determined by Inductively Coupled Plasma-Mass Spectrometry - Eid I. Brima (International Journal of Analytical Chemistry)
In terms of nutrition, dates are an important commodity because they are a source of carbohydrates and minerals. Saudi Arabia is the second largest producer of dates worldwide. Khalas is the tenth most popular date type in the Kingdom of Saudi Arabia (KSA), but only limited information related to the levels of essential nutrients in Khalas dates is available. The concentrations of Mn, Cu, Zn, and Se were determined using inductively coupled plasma-mass spectrometry (ICP-MS). The average concentrations in wet weight were as follows (mg/kg): Mn (2.90 ± 0.54), Cu (1.78 ± 0.64), Zn (1.72 ± 0.42), and Se (0.10 ± 0.06). The calculated intakes (μg/kg bw day) per 100 g dates for each element were as follows: Mn (4.14), Cu (2.54), Zn (2.46), and Se (0.14), which represent 0.14%, 0.51%, 0.25%, and 0.2%, respectively, of the provisional maximum tolerable daily intake (PMTDI) recommended by the EFSA/WHO. It was found that levels of the analysed essential elements in up to 100 g of Khalas dates do not exceed the level set by the EFSA/WHO.